Q-switched raman fiber laser based on 2D materials as saturable absorber / Najwa Hisamuddin - Najwa , Hisamuddin (2018)
This thesis aims to demonstrate a stable passively Q-switched Raman fiber laser (RFL) operated in C- band region by incorporating Two-dimension (2D) material inside the ring cavity as saturable absorber (SA) such as titanium dioxide (TiO2) and molybdenum disulfide (MoS2). 2D materials have been experimented to generate pulse laser due to their unique electronic and optical properties such as modulation depth, saturable absorption and their recovery time. First, we conducted an experiment for Q-switched RFL incorporating MoS2 based SA. The SA is prepared by depositing a mechanically exfoliated MoS2 on the end of the fiber ferrule which is then connected to another clean ferrule via an optical fiber adapter. The cavity consist of dispersion compensating fiber (DCF) with a 7.7 km length and 584 ps·nm−1 km−1 of dispersion as nonlinear gain medium for Q-switching pulse train generation. The total laser cavity length is about 8 km. The Q-switching pulse train operated at around 1560.2 nm with the repetition rate changed from 132.7 to 137.4 kHz as the input pump power is tuned from 395 to 422 mW, while the pulse width reduced from 3.35 to 3.03 μs. At the maximum pump power of 422 mW, the maximum pulse energy of 54.3 nJ is achieved. Next, we conducted a Qswitched RFL by replacing the MoS2 with TiO2 film based SA. We observed that the pulse train operated at 1558.5 nm is generated with the repetition rate that can be increased from 131.4 to 142.5 kHz as the input pump power changed from 398 to 431 mW. We noticed that the Q-switched pulse produced maximum energy of 5.81 nJ and pulse width of 2.97 μs at input pump power of 427 mW and 431 mW, respectively. These results verified that the TiO2 film and MoS2 has a strong capability to be employed as an effective SA for Q-switched RFL pulse generation system.